Dynamic evolutions of ecological carrying capacity in poor areas using ecological footprint model at Ruyang County of China - Jun, Wang; Qiaoming, Zhang; Chunjing, Zou; Jinxin, Wang; Yongsheng, Li; Mingchun, Wang (International Journal of Agricultural and Biological Engineering, 2017)
In this study, the ecological footprint (EF) from 2004 to 2013 of a poor county chosen from Central China was measured and analyzed by using the methodology and theory of EF. The results showed that in the past 10 years, the county’s ecological footprint per capita was growing gradually, increasing from 0.7053 hm2 in 2004 to 1.4473 hm2 in 2013, with growth clearly accelerated in recent years. During the same period, the ecological carrying capacity per capita reduced from 0.6351 hm2 to 0.5018 hm2. Additionally, regional development had been in a state of ecological deficit, per capita ecological deficit increased from 0.0702 hm2 to 0.9456 hm2. This led to contradictions between regional socio-economic development and sustainability of natural ecosystems, meaning the development of the region is unsustainable. Measures to reduce the ecological deficit were proposed to coordinate regional industrialization, urbanization, ecological environmental protection, and to promote the sustainable development in the region (e.g. adjusting industrial structure and consumption structure, promoting economic transformation, scientific planning and management of land). The results could provide a scientific basis for studies on ecological carrying capacity of the poor areas in Central China.Keywords: ecological footprint, ecological carrying capacity, ecological deficit, sustainable development, poor areas in ChinaDOI: 10.3965/j.ijabe.20171002.2109Citation: Wang J, Zhang Q M, Zou C J, Wang J X, Li Y S, Wang M C. Dynamic evolutions of ecological carrying capacity in poor areas using ecological footprint model at Ruyang County of China. Int J Agric & Biol Eng, 2017; 10(2): 140–150.